Visual Analysis of Ceramic Decoration in the Qianlong Period of Qing Dynasty using Heinrich Wölfflin 's and Erwin Panofsky's Methods - Ying, Li (Universiti Malaysia Sarawak, 2024)
During the Qianlong period of the Qing Dynasty, the development of Chinese ceramic decorative arts achieved rich results and created many exquisite ceramic decorative arts and forms. This study takes the ceramic decorative art of the Qianlong period of Qing Dynasty as the research object, using the method of formal analysis and iconography to study the ceramic decorative art of the Qianlong period. To determine the theme, artistic characteristics, form and symbolic meaning of ceramic decoration images in the Qianlong period of Qing Dynasty. Based on literature and image data, this study mainly uses Heinrich Wölfflin 's form analysis and Erwin Panofsky 's iconography research methods to classify ceramic decorative patterns and summarize the traditional meanings of decorative patterns, and explores the forms and artistic characteristics of decorative patterns from the perspective of analyzing the visual forms of artworks. Then the symbolic meaning of decorative patterns is explored by using the method of image science. The results show that the ceramic decorative patterns of Qianlong period can be divided into 9 types, and each type can be divided into many small categories. Each decorative pattern has a specific traditional Chinese cultural meaning. At the same time, these ceramic decorative patterns are very beautiful, with two artistic characteristics of complexity and gorgeousness. Finally, from the perspective of analyzing the background of politics, economy, culture and art, this paper summarizes the symbolic meaning of ceramic decorative patterns. In the past, domestic scholars' research on ceramic decoration during the Qianlong period mainly focused on the historical development of Chinese ceramics and the historical background of the development of Chinese ceramics. It rarely involves a comprehensive, systematic, multi-level image analysis of the ceramic decoration of a particular king, especially the Qianlong Emperor. Through the research, we can supplement more reference and basis for the study of ceramic decoration in Qianlong period academically, and provide some practical reference materials for students and lovers of ceramic art.